Some properties of Potato Virus M (PVM) in Crude Sap and in Pure Preparations - Ahmad, Ismail; Stace-Smith, R; Wright, N.S (1985)
A study was performed to determine some properties of the potato virus M (PVM) in crude sap and in pure preparations. In crude sap the virus was shown to have a dilution end point value of 10- 4, longevity in vitro particles sedimented as one peak with a sedimentation coefficient value of 162 s. The buoyant density in cesium chloride was 1.304 gm/cm ~ Electrophoresis in polyacrylamide gels showed that the virus possessed only one protein subunit with a molecular weight of 39,300 daltons.